Microsoft Office 2010 advanced - Shelly, Gary B. (Shelly Cashman series, 2011)
Offers step-by-step, screen-by-screen approach that encourages students to expand their understanding of the Office 2010 software through experimentation, exploration, and planning ahead. This title includes end of chapter exercises that prepare students to become capable software users